CD45 negatively regulates tumour necrosis factor and interleukin-6 production in dendritic cells. - Piercy, J; Petrova, S; Tchilian, E; Beverley, P (2006)
CD45 is known to regulate signalling through many different surface receptors in diverse haemopoietic cell types. Here we report for the first time that CD45-/- bone marrow dendritic cells (BMDC) are more activated than CD45+/+ cells and that tumour necrosis factor (TNF) and interleukin-6 (IL-6) production by BMDC and splenic dendritic cells (sDC), is increased following stimulation via Toll-like receptor (TLR)3 and TLR9. Nuclear factor-kappaB activation, an important downstream consequence of TLR3 and TLR9 signalling, is also increased in CD45-/- BMDC. BMDC of CD45-/- mice also produce more TNF and IL-6 following stimulation with the cytokines TNF and interferon-alpha. These results show that TLR signalling is increased in CD45-/- dendritic cells and imply that CD45 is a negative regulator of TLR and cytokine receptor signalling in dendritic cells.